Variety and Intra-Row Spacing On Growth and Yield of Potato (Solanum Tuberosum L) By Nigerian Farmers to Improve Productivity in Jos Plateau State, Nigeria - M. Anayib; E. Oiganji; P. S. Amaza; M. S. Abubakar; R. Z. Lenka (Journal of Applied Sciences and Environmental Management, 2025)
The objective of this paper was to evaluate the variety and intra-row spacing on growth and yield of Potato (Solanum tuberosum L.) by Nigerian farmers to improve productivity in Jos Plateau State, Nigeria during the 2024 rainy season using appropriate techniques. Data obtained show that the values of count, plant height, leaf area, stem girth at 30, 45, 60, and 75 days after planting; tuber number, length, diameter, and yield were assessed and results indicated no significant (p>0.05) effects on establishment count, plant height, tuber length, and diameter. However, significant (p≤0.05) effects were observed in leaf area, tuber number, weight, and yield. Marabel (variety 2) outperformed Connect, recording the highest yield (85,700kg/ha), with the 30×25cm spacing also yielding highest (72,375kg/ha). Hence, Marabel and 30×25cm spacing are recommended for potato cultivation.